2008
DOI: 10.2135/cropsci2007.08.0477
|View full text |Cite
|
Sign up to set email alerts
|

Novel Germplasm Resources for Improving Environmental Stress Tolerance of Hexaploid Wheat

Abstract: Wheat (Triticum spp. L.) breeders have significantly improved wheat adaptation to stress‐prone environments around the world. This progress has largely been achieved using empirical selection and genetic variability within the primary wheat gene pool. As most stress tolerance traits are quantitatively inherited, expansion of the available genetic diversity for stress tolerance is necessary if rates of genetic progress are to be maintained. This review explores three sources of novel genetic variability, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(133 citation statements)
references
References 91 publications
0
130
1
2
Order By: Relevance
“…Wheat breeding programs were established by all of the wheat-growing states, supplying new varieties and exchanging parental lines between breeding programs. These programs also established long-term collaborations with international institutes such as CIMMYT in Mexico to access the high-yielding wheats developed during the Green Revolution (Reynolds and Borlaug 2006) and, more recently, 'derived synthetic' wheats, which were created at CIMMYT by new methods to cross wild wheat relatives into durum and bread wheat germplasm (Trethowan and Mujeeb-Kazi 2008). Together with changes in the rotation and management of wheat crops, these domestic and international breeding efforts in Australia have contributed to a consistent increase in mean wheat yield of 1-2% per year for >70 years, despite the rainfall constraints in our wheat-growing regions (Fischer 2011) and soil.…”
Section: Accessing and Developing Useful Genetic Resources For Climatmentioning
confidence: 99%
“…Wheat breeding programs were established by all of the wheat-growing states, supplying new varieties and exchanging parental lines between breeding programs. These programs also established long-term collaborations with international institutes such as CIMMYT in Mexico to access the high-yielding wheats developed during the Green Revolution (Reynolds and Borlaug 2006) and, more recently, 'derived synthetic' wheats, which were created at CIMMYT by new methods to cross wild wheat relatives into durum and bread wheat germplasm (Trethowan and Mujeeb-Kazi 2008). Together with changes in the rotation and management of wheat crops, these domestic and international breeding efforts in Australia have contributed to a consistent increase in mean wheat yield of 1-2% per year for >70 years, despite the rainfall constraints in our wheat-growing regions (Fischer 2011) and soil.…”
Section: Accessing and Developing Useful Genetic Resources For Climatmentioning
confidence: 99%
“…Consequently, modern wheats developed from this original bottleneck [2]. An effective method to increase genetic diversity is to introgress chromosomal segments into the wheat genome from wild relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Breeding for these environments, where the frequency, timing, duration and severity of abiotic stresses, such as temperature extremes and drought, are unpredictable and variable, is considered slow and difficult (Passioura, 1986). However, A large body of recent work has demonstrated that new opportunities exist to improve the adaptation of wheat to heat and drought stressed environments (Trethowan and Mujeeb-Kazi, 2008;Rebetzke et al, 2009;Reynolds et al, 2010). The CIMMYT wheat program follows a system of breeding for drought tolerance in which yield responsiveness is combined with adaptation to drought conditions (Timothy et al, 2005).…”
Section: Optimum Environment For Selectionmentioning
confidence: 99%
“…Many recent works have showed that new opportunities exist to improve the adaptation of wheat to heat and drought stressed environments (Trethowan and Mujeeb-Kazi 2008;Rebetzke et al, 2009;Reynolds et al, 2010). Conventional breeding with a special focus on adaptation to marginal environments provides a necessary baseline in terms of genetic backgrounds into which new traits and their genes can be introduced.…”
Section: Indirect Selectionmentioning
confidence: 99%